SISTEM INFORMASI PENJUALAN HIPA ( HIMPUNAN PELUKIS AMBARAWA ) DI AMBARAWA SEMARANG BERBASIS WEB DENGAN E-COMMERCE (Information Technology and Telematics, 2013)
Sales   Information   System   at   UKM   OOX GUITAR MAKER is engaged in handicraft of guitar and another   musical  instrument.   UKM   OOX   GUITAR MAKER  often  joins  UKM exhibition  which  held  in central  java  province,  so  that  the guitar  and  another musical instrument are owned by UKM OOX GUITAR MAKER more widely known by the public. But  UKM OOX GUITAR MAKER has shortcomings or difficulties in selling their handicraft, while the works of UKM OOX GUITAR MAKER are sold only at the Gua Maria Kerep Ambarawa UKM.  Thus the author has the initiative to assist in the sale of their work with the help of internet media, namely the method E - COMMERCE.With the on-line  WEBSITE  by  the method of E - Commerce, can help them in selling their work to the whole world. In other words, the existence of such  program  expands  the  sales  area  by UKM  OOX GUITAR MAKER Ambarawa.Keywords:    Sales Information System, E - Commerce.